ANALISA KELAYAKAN USAHA PENGOLAHAN UBI KAYU MENJADI SELONDOK DESA BANJARHARJO KECAMATAN KALIBAWANG KABUPATEN KULON PROGO (ECONOMIC ANALYSIS OF PROCESSING SWEET POTATOS TO SELONDOK IN THE VILLAGE OF BANJARHARJO, KALIBAWANG SUBDISTRICT, DISTRICT OF KULON PR - Bharoto, Bharoto; Ariani, Koeswini Tri (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2010)
This study was conducted to analyze the feasibility work using profit analysis instrument, Return on Investment and O/I ratio. The study was conducted in the village of Banjarharjo, Kalibawang subdistrict, district of Kulonprogo. We got the sample using simple random sampling, that were 30 farmers that processed sweet potatos to selondok. The study was conducted in November 2009. Study results: we can conclude from the profit analysis, Return on Investment and output input ratio, that the processing work of sweet potatos to selondok is feasible and profitable. We got profit of Rp. 74,238 from the processing work of 100 kgs sweet potatos to 31 kgs selondok, and by assumption of processing them as much as 25 to 30 times a month, we could get profit between Rp. 1,855,950 to Rp. 2,227,140 a month. Analysis of Return on Investment (ROI), was 35% and Output Input ratio (I/O ratio) was 1,35.